Microbiome in Health: Establishment, Metabolism, Immunity and Neuronal Pathway - Ojezele, Matthew Obaineh; Ovuakporaye, Simon Irikefe; Adedapo, Emmanuel Adesola (Nepalese Medical Journal, 2020)
The studies on microbiome encountered a blast, lately, as scientists become mindful of the role of microbiota in the advancement of specifi c kinds of maladies. The human microbiome is described as a community of microorganisms of different taxa colonizing the human body; this includes the metagenomics and metabolomics of these organisms. Humans have customized microbiome in terms of distribution and composition which are partly determined by host genotype as well as the initial colonization which takes place after delivery. The human gut microbiome has a vital infl uence on immunity and how it responds to body signals, which is very important for the lymphoid tissue growth, maintenance, and regulation of intestinal immunity. This review aimed at providing an overview of the role of the human microbiome in health spanning the development of the microbiome in utero to postnatal period.